Digital Labor and the Sharing Economy: An Interview with Ivana Pais (interviewed by Ivan Pavlyutkin ) - Ivana Pais (Journal of Economic Sociology, 2016)
Prof. Ivana Pais was interviewed by Ivan Pavlyutkin, associate professor at the National Research University Higher School of Economics. The conversation occurred at the Department of Sociology of Catholic University of the Sacred Heart in Milan. Pais introduces us to her career path as an economic sociologist, and explains challenges that economic sociologists encounter while teaching economics students and why it is more insightful than teaching sociology students. She also talks about directions and peculiarities of economic sociological thought in Italy. There is a strong tradition in Italy to study industrial districts with their network of small firms and labor markets. In the interview, Pais shares her previous and current research projects. She points out the significance of the digital economy for a better understanding of some market processes happening within the local community and describes her current research concerning the sharing economy. Applying Karl Polany’s theoretical perspective, she argues that the Italian sharing economy is embedded in noneconomic institutions. A pure digital sharing economy model that lacks social interactions (the Silicon Valley type) does not work in Italy. Finally, Pais provides information about her participation in the conference arranged by the European commission and the organization of future mini-conference in Berkley.